Characterization of metastatic urothelial carcinoma via comprehensive genomic profiling of circulating tumor DNA. Issue 10 (8th March 2018) - Agarwal, Neeraj; Pal, Sumanta K.; Hahn, Andrew W.; Nussenzveig, Roberto H.; Pond, Gregory R.; Gupta, Sumati V.; Wang, Jue; Bilen, Mehmet A.; Naik, Gurudatta; Ghatalia, Pooja; Hoimes, Christopher J.; Gopalakrishnan, Dharmesh; et al.
Abstract : BACKGROUND: Biomarker‐guided clinical trials are increasingly common in metastatic urothelial carcinoma (mUC), yet patients for whom contemporary tumor tissue is not available are not eligible. Technological advancements in sequencing have made cell‐free circulating DNA (cfDNA) next‐generation sequencing (NGS) readily available in the clinic. The objective of the current study was to determine whether the genomic profile of mUC detected by NGS of cfDNA is similar to historical tumor tissue NGS studies. A secondary objective was to determine whether the frequency of genomic alterations (GAs) differed between lower tract mUC (mLTUC) and upper tract mUC (mUTUC). METHODS: Patients from 13 academic medical centers in the United States who had a diagnosis of mUC between 2014 and 2017 and for whom cfDNA NGS results were available were included. cfDNA profiling was performed using a commercially available platform (Guardant360) targeting 73 genes. RESULTS: Of 369 patients with mUC, 294 were diagnosed with mLTUC and 75 with mUTUC. A total of 2130 GAs were identified in the overall mUC cohort: 1610 and 520, respectively, in the mLTUC and mUTUC cohorts. In the mLTUC cohort, frequently observed GAs were similar between cfDNA NGS and historical tumor tissue studies, including tumor protein p53 ( TP53 ) ( P = 1.000 and .115, respectively), AT‐rich interaction domain 1A ( ARID1A ) ( P = .058 and .058, respectively), phosphatidylinositol‐4, 5‐bisphosphate 3‐kinase catalytic subunit alpha ( PIK3CA ) ( P = .058 and .067, respectively), erb‐b2 receptor tyrosine kinase 2 ( ERBB2 ) ( P = .565 and .074, respectively), and fibroblast growth factor receptor 3 ( FGFR3 ) ( P = .164 and .014, respectively). No significant difference was observed with regard to the frequency of GAs between patients with mLTUC and mUTUC. CONCLUSIONS: Among patients with mUC for whom no tumor tissue was available, cfDNA NGS was able to identify a similar profile of GAs for biomarker‐driven clinical trials compared with tumor tissue. Despite the more aggressive clinical course, cases of mUTUC demonstrated a circulating tumor DNA genomic landscape that was similar to that of mLTUC. Cancer 2018;124:2115‐24 . © 2018 American Cancer Society . Abstract : In patients with metastatic urothelial carcinoma, the mutational landscape detected by cell‐free circulating DNA (cfDNA) next‐generation sequencing (NGS) is similar to that of historical tumor tissue studies, and there appears to be no significant difference with regard to the frequency of genomic alterations detected between patients with metastatic lower tract urothelial carcinoma and those with metastatic upper tract urothelial carcinoma. This study demonstrates that cfDNA NGS can be used to identify genomic alterations for biomarker‐guided clinical trials in patients with metastatic urothelial carcinoma, especially when contemporary tumor tissue is not available.